Identification of β-propeller phytase-encoding genes in culturable Paenibacillus and Bacillus spp. from the rhizosphere of pasture plants on volcanic soils - Jorquera, Milko A; Crowley, David E; Marschner, Petra; Greiner, Ralf; Fernández, María Teresa; Romero, Daniela; Menezes-Blackburn, Daniel; De La Luz Mora, María (FEMS microbiology ecology, 2011)
Phytate is one of the most abundant sources of organic phosphorus (P) in soils, but must be mineralized by phytase-producing bacteria to release P for plant uptake. Microbial inoculants based on Bacillus spp. have been developed commercially, but few studies have evaluated the ecology of these bacteria in the rhizosphere or the types of enzymes that they produce. Here, we studied the diversity of aerobic endospore-forming bacteria (EFB) with the ability to mineralize phytate in the rhizosphere of pasture plants grown in volcanic soils of southern Chile. PCR methods were used to detect candidate phytase-encoding genes and to identify EFB bacteria that carry these genes. This study revealed that the phytate-degrading EFB populations of pasture plants included species of Paenibacillus and Bacillus, which carried genes encoding β-propeller phytase (BPP). Assays of enzymatic activity confirmed the ability of these rhizosphere isolates to degrade phytate. The phytase-encoding genes described here may prove valuable as molecular markers to evaluate the role of EFB in organic P mobilization in the rhizosphere.